Assessment of critical period for weeding and yield loss in direct seeded rice (Oryza sativa) - SINGH, TEEKAM (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted at research farm of Regional Rainfed Lowland Rice Research Station, ICARNational Rice Research Institute, Gerua, Assam during two consecutive boro seasons of 2014–15 and 2015–16 to assess yield losses in direct seeded rice (DSR) under weeding times. There were two DSR establishment techniques (dry and sprouted seeding) in main plots and four weeding times (15, 30, 45 and 60 DAS) in sub plots. It was found that Scirpus juncoides, Echinochloa colona, Cyperus difformis, Cyperus iria, Monochoria vaginalis and Ludwigia octovalvis were the dominant weed species in shallow lowlands. DSR establishment techniques had non-significant effect on weed characteristics as well as growth, yield attributes and productivity of rice. Weed density of individual weed group and dry matter were significantly influenced by weeding times. Weeding at 15 DAS resulted in significantly low weed density and biomass as compared to weeding at 45 and 60 DAS. Growth and yield attributes, viz. plant height, panicles/m2, filled grains/panicle and fertility percentage were significantly higher and subsequently resulted in higher grain and straw yield under early weeding at 15 DAS. The highest grain yield losses due to weeds were calculated with weeding at 60 DAS (20.4%) followed by 45 DAS (15.8%) in DSR. Thus, early weeding in DSR plays an important role to obtain higher productivity of rice and minimise yield loss due to weeds.